The Effect of Compound Exercises on the Non – dominant Arm on the Development of Scoring in Handball for Players aged (15 – 17) Years Old - Ali, Mudhar; Daroush, Amar (Journal of Physical Education, 2022)
The research aimed at deigning compound exercises for non – dominant arm on the development of scoring accuracy in handball players aged (15 – 17 years old as well as identifying their effect on the players. The researchers used the experimental method on (17) players aged 15 – 17 years old. The data was collected using SPSS to conclude that compound exercises have a significant effect on the development of scoring accuracy on handball players aged (15 – 17 years old. Finally, the researchers recommended dedicating time for skill exercises for non-dominant arms as well as using these exercises for developing scoring in handball players aged (15 – 17) years old.